2016
DOI: 10.1111/are.13050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density on growth performance and welfare‐related physiological parameters of Atlantic salmon S almo salar L. in recirculating aquaculture system

Abstract: Stocking density, representing a potential source of long‐term stress, is widely recognized as a critical factor in aquaculture husbandry. Atlantic salmon were reared at low‐density (LSD, ~9.80–18.41 kg m−3, initial to final density), medium‐density (MSD, ~19.62–36.96 kg m−3) and high‐density (HSD, ~28.79–53.54 kg m−3) stocking levels for 66 days to investigate the stress‐induced changes in fish growth and welfare. At the end of the trial, the salmon in HSD group showed significant lower final weight and highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…Such effects may be due to occurrence of oxidative stress and generation on reaction oxygen species and free radicals, which may induce haemolysis by attacking fatty acids at the RBC membrane. Supporting this hypothesis, increase in lipid peroxidation has been observed along with erythropaenia in the aforementioned studies (Battisti et al, 2020;Liu et al, 2017) and the present one. Therefore, it is speculated that dietary Stressful conditions lead to elevations in the blood cortisol and glucose levels, which have a variety of physiological effects in fish including providing energy resource (Barton, 2002).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Such effects may be due to occurrence of oxidative stress and generation on reaction oxygen species and free radicals, which may induce haemolysis by attacking fatty acids at the RBC membrane. Supporting this hypothesis, increase in lipid peroxidation has been observed along with erythropaenia in the aforementioned studies (Battisti et al, 2020;Liu et al, 2017) and the present one. Therefore, it is speculated that dietary Stressful conditions lead to elevations in the blood cortisol and glucose levels, which have a variety of physiological effects in fish including providing energy resource (Barton, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…Blood haematological parameters are applicable indicators of fish health, which change during stress and diseases or in response to dietary additives (Clauss et al, 2008). A number of studies have demonstrated that unfavourable stocking densities induces erythropaenia and/or decrease in the blood haematocrit and haemoglobin in different fish species (Battisti et al, 2020; Liu et al, 2017), including common carp (Abdel‐Tawwab et al, 2021). Such effects may be due to occurrence of oxidative stress and generation on reaction oxygen species and free radicals, which may induce haemolysis by attacking fatty acids at the RBC membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes denote a more intensive smolt production. High stocking densities are associated with higher stress response of fish (Ellis et al, 2002;Liu et al, 2017). In addition, it can make it difficult to maintain good water quality, leading to chronic stress which affects the immune system (Sundh et al, 2019).…”
Section: Mortality Varies Between Yearsmentioning
confidence: 99%
“…Rearing density is a critical factor for intensive aquaculture productivity, with suboptimal conditions known to impact fish, from growth (8,9) and quality (16) to health (17, 19) and welfare (9,30,31,42). Here, we used a transcriptome-wide approach to assess the effect of rearing density on pathogen responses in Atlantic salmon, revealing suppression of immunologically-important gill gene expression responses at high density.…”
Section: Discussionmentioning
confidence: 99%
“…High density salmon (four-fold higher than "low-density" treatment, though still within recommended welfare limits (44)) had increased expression of key markers for stress in vertebrates including c-fos (45)(46)(47) and hsp70 (48,49). Previous studies on the effects of rearing density on immunity in salmonids have primarily focussed on levels of serum antibodies (typically IgM) or antibody-producing cells, with suppression generally found at higher densities (8,36). In addition, non-specific innate immune markers such as serum lysozyme activity have been shown to be influenced by rearing density (42).…”
Section: Discussionmentioning
confidence: 99%